2018
DOI: 10.1038/s41598-018-27283-7
|View full text |Cite
|
Sign up to set email alerts
|

Straight motion of half-integer topological defects in thin Fe-N magnetic films with stripe domains

Abstract: In thin magnetic films with perpendicular magnetic anisotropy, a periodic “up-down” stripe-domain structure can be originated at remanence, on a mesoscopic scale (~100 nm) comparable with film thickness, by the competition between short-range exchange coupling and long-range dipolar interaction. However, translational order is perturbed because magnetic edge dislocations are spontaneously nucleated. Such topological defects play an important role in magnetic films since they promote the in-plane magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(74 reference statements)
1
8
0
Order By: Relevance
“…We obtained K PMA in the range from 5 to 7×10 6 erg cm −3 (see figure 7(c) later on), consistent with the reported values for the magnetocrystalline anisotropy of α′-Fe 8 N 1−x [85,86], and in agreement with K PMA values measured by ferromagnetic resonance [87]. We note that, assuming M s =1700 emu cm −3 [31], the quality factor Q of the Fe-N samples investigated in this work is between 0.275 and 0.385, depending on the preparation conditions, while the critical thickness above which the stripe domains appear is about 40 nm.…”
Section: Structural Investigationssupporting
confidence: 90%
See 2 more Smart Citations
“…We obtained K PMA in the range from 5 to 7×10 6 erg cm −3 (see figure 7(c) later on), consistent with the reported values for the magnetocrystalline anisotropy of α′-Fe 8 N 1−x [85,86], and in agreement with K PMA values measured by ferromagnetic resonance [87]. We note that, assuming M s =1700 emu cm −3 [31], the quality factor Q of the Fe-N samples investigated in this work is between 0.275 and 0.385, depending on the preparation conditions, while the critical thickness above which the stripe domains appear is about 40 nm.…”
Section: Structural Investigationssupporting
confidence: 90%
“…Weak stripe domains were first predicted theoretically [32,33] and later discovered experimentally in NiFe films [19,34]. In the following years, the phenomenon has been found and deepened in different kinds of thin films with moderate PMA, such as FeGa [35][36][37][38], FeN [31,39,40], FeSiB [41,42], CoFeB [43], FeTaN [44], GdFe [45], NdCo [46], FeCoZr [23], La x Sr 1−x MnO 3 [47] and multilayers with moderate perpendicular anisotropy [48][49][50]. Very recently, it has been shown [51] that the formation of stripe domains can be induced in a Py film, even far below the critical thickness, by coupling the Py film to a NdCo one, characterized by a moderate PMA.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Here, we employ spin polarized scanning tunneling microscopy (STM) to study pinning of the curled magnetization of a magnetic vortex core 22,23 . We apply well defined lateral forces by in-plane magnetic fields B ∥ 24 and independently tune the size of the vortex core by an out-of-plane field B ⊥ . The latter enables control on the non-collinearity of the core magnetization and, hence, on the strength of exchange energy density u exch in the core.…”
mentioning
confidence: 99%
“…4 (a)), have been commonly observed in several magnetic textures, including ferromagnetic stripe, helical, and skyrmion domain structures. Previous studies have reported the dynamics of topological defects in these magnetic textures under thermal fluctuation or a magnetic field 17,[27][28][29] .…”
Section: Simulation Of Inline Holography For Dynamics Of Topological Defectsmentioning
confidence: 99%